1999
DOI: 10.1038/sj.bjc.6690774
|View full text |Cite
|
Sign up to set email alerts
|

Single-agent gemcitabine in pretreated patients with non-small-cell lung cancer: results of an Argentinean multicentre phase II trial

Abstract: The activity and mild toxicity profile of single-agent gemcitabine therapy in untreated (chemonaive) patients with non-small-cell lung cancer (NSCLC) is well documented. This phase II trial was conducted to determine the objective tumour response rate and toxicity profile of single-agent gemcitabine in pretreated patients with NSCLC. Patients with histological evidence of advanced NCSLC stage IIIB or IV; at least one prior chemotherapy regimen including a platinum or taxane analogue; an Eastern Cooperative Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
1
3
1
Order By: Relevance
“…In phase II trials, the response rate to single-agent gemcitabine as second-line therapy for NSCLC has ranged from 6.0-20.6%; median survival has ranged from 4-7.9 months. [6][7][8][9][10] The present study revealed a response rate of 12.5% and a median survival of 7.5 months; these values are within the aforementioned ranges. The toxicity of single-agent gemcitabine therapy has been minimal and mild in severity, both in the present and previous studies.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In phase II trials, the response rate to single-agent gemcitabine as second-line therapy for NSCLC has ranged from 6.0-20.6%; median survival has ranged from 4-7.9 months. [6][7][8][9][10] The present study revealed a response rate of 12.5% and a median survival of 7.5 months; these values are within the aforementioned ranges. The toxicity of single-agent gemcitabine therapy has been minimal and mild in severity, both in the present and previous studies.…”
Section: Discussionsupporting
confidence: 78%
“…The toxicity of single-agent gemcitabine therapy has been minimal and mild in severity, both in the present and previous studies. [6][7][8][9][10] The present trial also identified a median survival time of 4.5 months, together with very mild toxicity, in the 17 patients receiving gemcitabine as third-line therapy. This finding warrants further clinical study, even though median survival was shorter than that reported for daily, oral gefitinib therapy in the Iressa ® Dose Evaluation in Advanced Lung Cancer (IDEAL)-2 study, in which previous platinumbased combination chemotherapy and docetaxel regimens had also failed.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The good results shown in our and Cho's and Crino's studies [10,11] would suggest selection of patients with good performance status is an important predictive factor of second-line gemcitabine therapy for response and longer survival. Beside performance status, it was suggested that there are also some poor prognostic factors which may affect response to second-line therapy including metastatic disease, number of metastatic sites and previous response to first-line chemotherapy [11][12][13]. In our study, although not statistically significant due to small number of patients, there was no objective response and only one stable disease in patients with more than two metastatic sites (Table 1).…”
Section: Discussioncontrasting
confidence: 67%
“…Although there was no randomized study comparing single agent gemcitabine with best supportive care or other agents known to be effective in the second-line setting, its activity has been investigated in several small studies and discordant ratios of objective response ranging from 6% to 20%, 6% have been reported [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 97%